Regulation of mucosal lectins in the oyster Crassostrea virginica in response to food availability and environmental factors. (8th December 2020) - Allam, Simon; Allam, Bassem; Pales Espinosa, Emmanuelle
ABSTRACT: Lectins are a large and diverse group of sugar-binding proteins involved in nonself recognition and cell-to-cell interactions. Suspension-feeding bivalves, such as the oyster Crassostrea virginica, are capable of using these molecules to bind cell surface carbohydrates of food particles, allowing particle capture and selection. The aim of this project was to assess whether the expression of mucosal lectins in C. virginica is constant or changes with the season, and to determine whether lectin expression is linked to environmental parameters and/or internal biological factors (gametogenesis). A total of 130 oysters were placed in submerged cages at a tidal estuary and monitored for changes in lectin gene expression over a 1-year period. In parallel, environmental parameters prevailing at the field site, including seawater physicochemical characteristics (temperature, salinity and dissolved oxygen), particulate organic matter and chlorophyll contents, were also monitored. Throughout the study, oysters were dissected and the gills were collected and used for the assessment of the expression of three different lectin genes (CvML, CvML3914 and CvML3912). Remaining tissues were processed for histology and the classification of the gonad development stage. Results showed that when food is abundant, such as during the spring bloom, lectin gene expressions are low, and inversely lectin levels increase with lower food levels. These findings suggest that oysters increase lectin expression to enhance the capture and ingestion of scarce food, while during spring, enough food is already being ingested and lectins are not needed. Furthermore, results showed that as the energy demands of oysters increase (gonad maturation), lectin gene expressions also increase to enhance selective ingestion of nutritious food particles. This study, therefore, demonstrates the seasonality of lectin gene expression in C. virginica, and suggests that lectin regulation is related to the reproduction process and abundance of high-quality food.